2010
DOI: 10.3233/nre-2010-0567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of motor imagery training on symmetrical use of knee extensors during sit-to-stand and stand-to-sit tasks in post-stroke hemiparesis

Abstract: Objective: To investigate the effect of motor imagery training (MIT) on the symmetrical use of knee extensors during sit-to-stand and stand-to-sit tasks. Methods: We measured the electromyographic (EMG) data in the knee extensor on the affected side of 3 volunteers with poststroke hemiparesis. We used a single-subject multiple-baseline research design across individuals. The EMG data were collected from knee extensors while performing the sit-to-stand and stand-to-sit tasks. The EMG activation and onset time r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
2
12
0
1
Order By: Relevance
“…Lomaglio and Eng [25] reported that paretic muscle strength and the ability to load the paretic limb are important factors underlying the ability to rise from a chair in individuals with chronic stroke. Recently, motor imagery of STS movement for individuals with stroke has been introduced by some researchers [10,11]. Previous studies have reported that the application of motor imagery practice can be an effective means of enhancing STS movement for treatment of hemiplegic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lomaglio and Eng [25] reported that paretic muscle strength and the ability to load the paretic limb are important factors underlying the ability to rise from a chair in individuals with chronic stroke. Recently, motor imagery of STS movement for individuals with stroke has been introduced by some researchers [10,11]. Previous studies have reported that the application of motor imagery practice can be an effective means of enhancing STS movement for treatment of hemiplegic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Malouin et al [9] found that after just one session of motor imagery training in an STS task, 12 stroke patients demonstrated an enhancement of weight bearing on the paretic lower limb while standing, with the improvement maintained after 24 hours. Oh et al [10] reported that motor imagery training has a positive effect on the symmetrical use of knee extensors during STS and stand-to-sit tasks. Guttman et al [11] suggested that the imagery practice of meaningful motor tasks can positively affect real performance, including STS and reaching to grasp objects.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a gain in movement speed without an increase in limb loading on the affected side after MI training of sit-to-stand (Guttman et al, 2012) suggests that the MI training protocol did not promote the learning of the novel motor strategy. Likewise, the use of the knee extensor muscle activity (EMG alone) as an indicator of vertical force distribution between the paretic and non-paretic limbs as a means of assessing an improved motor strategy can be questioned (Oh et al, 2010), and requires prior validation.…”
Section: Factors Influencing MI Training Outcomesmentioning
confidence: 99%
“…Technical support is also used at times to illustrate what should be imagined. Mirror therapy (Ietswaart et al, 2011) or watching videos to learn about walking, or to identify their own gait problems from videos taken at different intervals (Hwang et al, 2010; Lee et al, 2011) and interacting with a computer and hardware devices for visual feedback of limb loading during a familiarization period in the first training session (Malouin et al, 2004a,b, 2009; Oh et al, 2010) are examples. It can involve actively imagining with the use of mirrors (Stevens and Stoykov, 2003; Ietswaart et al, 2011) or computer-facilitated imagery (Stevens and Stoykov, 2003).…”
Section: Factors Influencing MI Training Outcomesmentioning
confidence: 99%
“…For example, motor imagery has been used to improve strength, speed of action, range of motion, and posture in healthy individuals and athletes, as well as skilled actions in nursing and surgery (Dicksten & Deutsch, 2007). Motor imagery has also been shown to aid in rehabilitation of motor movement in patients suffering or recovering from stroke, spinal cord injury, and Parkinson's disease (Zimmermann-Schlatter 2008; Oh et al 2010; Tamir et al 2007; Dickstein & Deutsch, 2007). Repeated motor imagery practice increases motor-related activation of premotor, primary motor, and superior parietal regions in stroke patients (Page et al 2009a).…”
Section: The Motor Systemmentioning
confidence: 99%